"It's hard for us men to go to the clinic. We naturally have a fear of hospitals.": men's risk perceptions, experiences and program preferences for PrEP ; a mixed methods study in Eswatini - Berner-Rodoreda, Astrid; Geldsetzer, Pascal; Bärnighausen, Kate; Hettema, Anita; Bärnighausen, Till; Matse, Sindy; McMahon-Rössle, Shannon A. (PLOS ONE, 2020)
Few studies on HIV Pre-Exposure Prophylaxis (PrEP) have focused on men who have sex with women. We present findings from a mixed-methods study in Eswatini, the country with the highest HIV prevalence in the world (27%). Our findings are based on risk assessments, in-depth interviews and focus-group discussions which describe men's motivations for taking up or declining PrEP. Quantitatively, men self-reported starting PrEP because they had multiple or sero-discordant partners or did not know the partner's HIV-status. Men's self-perception of risk was echoed in the qualitative data, which revealed that the hope of facilitated sexual performance or relations, a preference for pills over condoms and the desire to protect themselves and others also played a role for men to initiate PrEP. Trust and mistrust and being able or unable to speak about PrEP with partner(s) were further considerations for initiating or declining PrEP. Once on PrEP, men's sexual behavior varied in terms of number of partners and condom use. Men viewed daily pill-taking as an obstacle to starting PrEP. Side-effects were a major reason for men to discontinue PrEP. Men also worried that taking anti-retroviral drugs daily might leave them mistaken for a person living with HIV, and viewed clinic-based PrEP education and initiation processes as a further obstacle. Given that men comprise only 29% of all PrEP users in Eswatini, barriers to men's uptake of PrEP will need to be addressed, in terms of more male-friendly services as well as trialing community-based PrEP education and service delivery.
Gesehen am 11.12.2020